2022
DOI: 10.1001/jamasurg.2022.3135
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Level Racial and Ethnic Segregation Among Medicare Beneficiaries Undergoing Common Surgical Procedures

Abstract: This cohort study uses Medicare fee-for-service claims data to assess hospital-level racial and ethnic segregation among beneficiaries undergoing common surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 7 publications
3
24
0
Order By: Relevance
“…[42][43][44] At the system level, racial residential and hospital level segregation in conjunction with modern health care system financing such as insurance price discrimination has contributed to the concentration of racial and ethnic minority groups at lower volume and lower quality hospitals for their surgical care. 8,13,[45][46][47][48][49] For instance, the significantly higher payment in services from private health insurers compared with Medicare and Medicaid, creates incentives for hospitals to provide care to populations that are with larger shares of privately insured patients. 26 This has…”
Section: Societal Inequities In Resource Allocation Contribute To Ine...mentioning
confidence: 99%
See 4 more Smart Citations
“…[42][43][44] At the system level, racial residential and hospital level segregation in conjunction with modern health care system financing such as insurance price discrimination has contributed to the concentration of racial and ethnic minority groups at lower volume and lower quality hospitals for their surgical care. 8,13,[45][46][47][48][49] For instance, the significantly higher payment in services from private health insurers compared with Medicare and Medicaid, creates incentives for hospitals to provide care to populations that are with larger shares of privately insured patients. 26 This has…”
Section: Societal Inequities In Resource Allocation Contribute To Ine...mentioning
confidence: 99%
“…This has implications for racial and ethnic inequities in care given that non-Hispanic Black and Hispanic patient populations are disproportionately enrolled in Medicaid, whose access to surgical services, particularly surgical subspeciality care, may be limited given lower reimbursement 49 . Furthermore, recent analysis has demonstrated that <25% of hospitals in the United States perform 90% of surgeries for American Indian/Native Americans, Asian and Pacific Islander, Hispanic, and non-Hispanic Black patients with those hospitals having worse outcomes 13 …”
Section: Definitions and Mechanisms Of Racial And Ethnic Inequities I...mentioning
confidence: 99%
See 3 more Smart Citations